PENGARUH RELAKSASI DEEP BREATHING DENGAN TEKNIK SELF INTRODUCTION TRAINING (SIT) DALAM BENTUK AUDIO VISUAL TERHADAP KECEMASAN PADA IBU HAMIL - Sukma Adnyani; Ni Nyoman Deni Witari; Ni Nyoman Ayuk Widiani (LPPM Universitas Abdurrab, 2024)
Anxiety during pregnancy is related to a state of worry in the form of fear or feelings of uncertainty or helplessness and if not treated it can pose a risk to pregnancy. A non-pharmacological approach that can be given to pregnant women is relaxation therapy. Deep breathing relaxation therapy is a relaxation technique that is easiest to apply without having to use an instructor. This technique can be combined with the self-instruction technique, which is a self-verbalization technique by replacing negative thoughts with positive thoughts. The aim of this research is to analyze the comparison of the effectiveness of deep breathing relaxation using the Self Instruction Training technique via audio-visual with the effectiveness of deep breathing relaxation using audio only. The research method used was quasi experimental with the Pretest-Posttest Control Group design technique. The anxiety measuring tool is determined using the State – Trait Anxiety (STAI) tool which is presented in the form of a questionnaire form. The population in this study were pregnant women in the TPMB working area of East Denpasar Community Health Center I. The sampling technique used is accidental sampling. The sample in this study was 30 pregnant women at TPMB Bdn. Ketut Nuriasih, S.ST and TPMB Ni Made Serioni, A.Md. Keb. Based on data analysis using Mann Whitney, a p value of 0.003 was obtained, where the p value was <0.005, which means there was a significant difference in the effectiveness of the final anxiety level in pregnant women who were given deep breathing relaxation audio and pregnant women who were given deep breathing relaxation video using the SIT (Self) method. Instruction Training). For pregnant women, it is hoped that this research will provide benefits as additional knowledge regarding the use of deep breathing relaxation in audio-visual form to relieve discomfort during pregnancy.